1999
DOI: 10.1016/s0370-2693(99)01075-8
|View full text |Cite
|
Sign up to set email alerts
|

A next-to-next-to-leading-order pp→ppπ0 transition operator in chiral perturbation theory

Abstract: We discuss the results of a systematic calculation of the next-to-next-to-leading-order amplitude for the pp → ppπ 0 S-wave production at the threshold in heavy-baryon chiral perturbation theory. We find six new diagrams, two of which can be viewed as vertex corrections, of 15 -20 %, to the π-exchange graph, whereas the rest are much larger, one exceeding 900 %. We discuss the reasons for this enhancement, as well as the steps necessary to be taken before the final comparison with experiment.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 27 publications
8
65
0
Order By: Relevance
“…[14], in Ref. [20] it was shown that it is allowed to expand the integrand of the loop integrals before evaluation in powers of m π /M .…”
Section: Evaluation Of Loopsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14], in Ref. [20] it was shown that it is allowed to expand the integrand of the loop integrals before evaluation in powers of m π /M .…”
Section: Evaluation Of Loopsmentioning
confidence: 99%
“…At the same time it was already realized that a modified power counting is nescessary to properly take care of the large momentum transfer characteristic for pion production in N N collisions, however, when applied in its original formulation the results were basically the same for neutral [12] as well as charged pions [13]. Even worse, the corrections at oneloop order (next-to-next-to-leading order (N 2 LO) in the standard counting) turned out to be even larger than the NLO corrections, indicating a divergence of the chiral expansion [14,15].…”
Section: Introductionmentioning
confidence: 97%
“…[2,[7][8][9][10][11], did not only fail to describe the data, especially in the pp → ppπ 0 channel, but also revealed a problem with the convergence of the chiral expansion. However, in Ref.…”
Section: Introductionmentioning
confidence: 98%
“…The fact that low-and medium-energy strong interactions are controlled by chiral symmetry led to an early hope that chiral effective theories could be used to analyze these processes and achieve a fundamental understanding of the production process. Indeed, there are now tree level calculations [2][3][4][5][6][7] and even loop calculations [8][9][10] available in the literature [11]. The early excitement was quickly abated by the realization that proper evaluation involves surmounting several severe difficulties, which are caused by the high momentum transfer nature of this threshold process.…”
Section: Introductionmentioning
confidence: 99%